Color tunable upconversion luminescent perovskite fluoride with long-/short-lived emissions toward multiple anti-counterfeiting. Issue 27 (18th June 2019) - Han, Xinxin; Song, Enhai; Zhou, Bo; Zhang, Qinyuan
Abstract : A color-tunable UC luminescent perovskite fluoride KCdF3 :Yb 3+, Mn 2+, Ln 3+ with both long and short emission lifetimes has been demonstrated, showing high potential for multiple anti-counterfeiting with high throughput authentication rate. Abstract : In contrast to simply static fluorescence, the introduction of time-resolved visualized fluorescence in materials can significantly improve their anti-counterfeiting performance; however, this remains challenging with photon upconversion (UC) luminescent materials. Herein, we demonstrate a color-tunable UC luminescent perovskite fluoride KCdF3 :Yb 3+, Mn 2+, Ln 3+ (Ln 3+ = Er 3+, Ho 3+, Tm 3+ ) with both long (∼20–40 ms) and short (∼0.4–2 ms) emission lifetimes. Under steady 980 nm laser excitation, color-tunable steady UC fluorescence from yellow to red (or green) and yellow to blue (including UC white emission) could be easily achieved by tuning the doping concentration of Mn 2+ and Ln 3+ in the system; whereas, an unalterable yellow UC afterglow was observed by the naked eye when the excitation source was removed. Moreover, the upconversion nanoparticles (UCNPs) exhibited excellent pump power- and temperature-dependent luminescence stability. Static and dynamic photoluminescence analysis provided an understanding of the unique UC luminescence in this system, and a bidirectional energy transfer UC mechanism between Mn 2+ (or Yb 3+ –Mn 2+ dimer) and Ln 3+ is presented. The multiple anti-counterfeiting prototype using the unique UC luminescent materials demonstrated a high throughput authentication rate without the need for complex, time-gated decoding instrumentation, suggesting their high potential for anti-counterfeiting application, and also providing new insights for the design of photon UC luminescence materials.